HUBUNGAN EFEKTIFITAS PSB SMA ONLINE DAN KINERJA WEBSITE TERHADAP KEPUASAN USER DIWILAYAH DINAS PENDIDIKAN KOTA PADANG - Mutia Rafika Afsah; Muhammad Adri; Ahmaddul Hadi (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2015)
The growth of  information  technology is  increasing rapidly, the need for  proper  information, fast and accurate is the desire of everyone.  As well as online admission  of  new  students (PSB) is a product of real time software application  services and 100% web-based. However, there is no significant relationship exists between the effectiveness and performance of the website by the user. Seeing these symptoms then  it can defined  problems in this research whether there is a significant correlation between the effectiveness of PSB Online and website performance together with user satisfaction in the area of Department of Education on Padang city.The research hypothesisis that there is a positive and significant influence together between the effectiveness of PSB Online with website performance against user satisfaction.This research using survey research approach with descriptive correlations methods to see a significant correlation between the effectiveness of PSB Online and website performance together with user satisfaction in the area of Department of Education on Padang city. Research population is public senior high school studentsin thearea of Department of Education on Padang cityandsampling technique is simple random sampling so the sample was 100 respondents.From the researchit appears that the effectiveness of online PSB has a positive relationshipby76.10%. Website performance has a positive correlation by86.70%. Effectiveness and performance PSB online websites together has a positive relationship by 90.50%. From the finding research data, it could be seen the level of achievement of the respondents to the effectiveness of online PSB included both categories andals othe website performance in both categories. Keywords: Relationships, effectiveness, performance, website, user